Stress Experiences and Coping Strategies Associated to Signs of Depression in Patients with Chronic Disorders - Noviyanti, Laura Khattrine; Ryandini, Felicia Risca (Indonesian Journal of Global Health Research, 2024)
Chronic disease is the disease that causes the most deaths in the world. In 2020, 73% of deaths that occur in the world will be due to chronic diseases. The purpose of this research is to find out. The general aim of this research is to find out the phenomenological study of the formation process of depression in chronic disease. Qualitative research method with a phenomenological approach. Participants used as many as ten patients. The results of the study average an average age of 52–90 years; the majority are female, and most of the education is elementary school. The results of the study obtained six themes, including my life situation, which made me depressed; my feeling of pressure, which was almost numb; changes in my activities after being sick; my helpless physical condition; my self-defense, which was formed so that I would not be depressed; my efforts to recover quickly.